2016
DOI: 10.1080/21645515.2017.1264796
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for pneumonia, invasive diseases and otitis in Tuscany (Italy), 2002-2014: Which was the impact of universal pneumococcal pediatric vaccination?

Abstract: Streptococcus pneumoniae is the main causative organism of acute media otitis in children and meningitis and bacterial pneumonia in the community. Since 2008 in Tuscany, central Italy, the pneumococcal conjugate vaccine (7-valent vaccine, switched to 13-valent vaccine in 2010) was actively offered free of charge to all newborns. Aim of the study is to evaluate the impact of pneumococcal pediatric vaccination in the Tuscan population on hospitalizations potentially caused by S. pneumoniae, during pre-vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…Similar increases in population aged above 64 years were reported in other European countries [3032]. Our findings, alongside recent economic considerations [33] further support the introduction of a pneumococcal vaccination strategy targeting individuals aged above 64 years in Italy included in the latest NPVP released in 2017 [6]. Despite the plan ambitiously set a 75% target VC to be achieved by 2019, available data indicate much lower coverage level achieved so far.…”
Section: Discussionsupporting
confidence: 83%
“…Similar increases in population aged above 64 years were reported in other European countries [3032]. Our findings, alongside recent economic considerations [33] further support the introduction of a pneumococcal vaccination strategy targeting individuals aged above 64 years in Italy included in the latest NPVP released in 2017 [6]. Despite the plan ambitiously set a 75% target VC to be achieved by 2019, available data indicate much lower coverage level achieved so far.…”
Section: Discussionsupporting
confidence: 83%
“…Tuscany, a region in central Italy with about 3.7 million of inhabitants, reported 74 cases in 2016 and 53 in 2017 with a notification rate of 2.0 cases per 100,000 inhabitants in 2016 and 1.4 in 2017. This finding is below the European mean incidence of 5.4 cases per 100,000 in 2016 and 6.2 in 2017 and divergent from previous studies that reported higher levels of hospitalization for IPD in Tuscany [ 16 ]. These observations have pointed toward the need for an assessment of the quality of the IPD surveillance system currently in place in Tuscany [ 15 , 17 ].…”
Section: Introductioncontrasting
confidence: 90%
“…In contrast to Germany, Iceland, Israel, South Korea, Australia, and the U. S., where the over 64 adult pneumococcal vaccination rate is above 50% ( Table 1 ), in the Liguria region of Italy, it was between 26 and 31% [ 168 ]; 24.9% in Calabria (“among the highest in Italy”) [ 170 ]; 20% in the Friuli Venezia Giulia region [ 171 ]; 15.4% in Veneto [ 172 ]; and averaged only 5% per year in each of ten years in the Italian region of Puglia, reaching a cumulative total of no more than 24–30% [ 173 ]. In consequence, even as infant rates of IPD have been falling in recent years, rates among adults over 64 have been increasing and now account for more than two-thirds of all cases in Italy [ 87 , 88 , 151 ]. Thus, the lack of protection against IPD afforded by infant PCV13 vaccination in Italy makes perfect sense in the context of the shift of IPD-responsible serotypes to non-covered ones among adults and the very low rates of pneumococcal vaccination among those adults.…”
Section: Discussionmentioning
confidence: 99%
“…A second dataset was accumulated to compare the importance of childhood pneumococcal [88], measles-mumps-rubella [150], and adult influenza [49] vaccination rates on rates of invasive pneumococcal disease [87,88,151] and COVID-19 death rates [152] in the twenty-one regions of Italy. Rates of adult pneumococcal and other vaccinations such as polio, diphtheria, and BCG were not found for more than a handful of regions despite a dedicated search of both PubMed and Google and were insufficient to support statistical analysis.…”
Section: Italian Regional Datamentioning
confidence: 99%
See 1 more Smart Citation